2013
DOI: 10.2478/s11535-013-0179-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes in the liver of Chelidonichthys obscurus from the Montenegrin coastline

Abstract: The activities of antioxidant defence enzymes — total, manganese and copper zinc containing superoxide dismutase (Tot SOD, Mn SOD, CuZn SOD), catalase (CAT), glutathione peroxidase (GSH-Px), glutathione reductase (GR) and biotransformation phase II enzyme glutathione-S-transferase (GST) — in the liver of longfin gurnard (Chelidonichthys obscurus) from the Montenegrin coastline (Adriatic sea) were investigated. The specimens were collected in winter (February) and late spring (May) at two localities: Platamuni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Some researchers showed that the biotransformation phase II enzyme GST is influenced by the levels of organic substrates, and both increased and inhibited enzyme activities have been reported in field studies. A similar increase in GST activity in winter was obtained by us in the liver of both thinlip gray mullet (Liza ramada) and longfin gurnard (Chelidonichthys obscurus) [18,31].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Some researchers showed that the biotransformation phase II enzyme GST is influenced by the levels of organic substrates, and both increased and inhibited enzyme activities have been reported in field studies. A similar increase in GST activity in winter was obtained by us in the liver of both thinlip gray mullet (Liza ramada) and longfin gurnard (Chelidonichthys obscurus) [18,31].…”
Section: Discussionsupporting
confidence: 71%
“…The concentrations of all other classes of PAHs were below 50 ng/L. We also measured five heavy metals (Mn, Zn, Cu, Co, Ni) and no significant seasonal differences were observed [16,31]. It can be concluded that the investigated pollutants had a similar distribution during both seasons (except phenantrene), and that it is difficult to predict the direct influence of these compounds on the antioxidant defense.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…SOD converts O 2 − to O 2 and H 2 O 2 first, and then CAT catalyzes H 2 O 2 to harmless H 2 O and O 2 at random. As an important peroxidase decomposition enzyme, GSH-Px catalyzes other harmful peroxides in the body and reduces toxic peroxides to non-toxic hydroxyl compounds, to protect the structure and function of cell membranes of living organisms [44,45]. MPO is a marker of neutrophil function and activation, and the peroxidase activity of MPO generates hypochlorite to kill microbes and inactivate inhibitors of lytic enzymes.…”
Section: Antioxidant Enzyme Activitiesmentioning
confidence: 99%